Significance of Effective Communication in English of Tourism Professionals - Rajadurai, S. (University of Colombo, 2015)
Communication plays a key role in one's personal and professional life. Effective communication in English is important for two main reasons. Firstly, international business depends on it for its global markets and partnerships, and secondly tourism depends, for its sustainability, on a variety of professionals efficient in communication. Tourism, a laborintensive service industry has become a booming industry in Sri Lanka with the restoration of peace since 2010. It is one of the major contributors to the economy of Sri Lanka, and is also a promising industry generating a wide range of career opportunities for the youth. When it concerns the undergraduates and students of the three-year Diploma in Tourism and Hospitality Management offered by universities, namely Sabaragamuwa University, Rajarata University, University of Colombo, Sri Lanka Institute of Tourism and Hotel Management (SLITHM) and its nine satellite schools across the island, Mt. Lavinia International Hotel School, English for Specific Purposes (ESP) has not been focused on since none of these institutions are aware of the specific needs of the learners in the tourism context. As a result, teaching English has failed to address the specific needs of the students. This study focuses on the specific needs of the communication skills of a target group of learners and also professionals who are already in service in the tourism industry using English for communication within the domain of tourism. This study therefore proposes to assess the communicative skills and competences of the tourism professionals through needs analysis in order to investigate the purposes of learning English, the existing language proficiency and the target language proficiency of various categories of tourism professionals: undergraduates, managers, tour guides and tourist police. Based on the results, an effective course in English is suggested within the frame work of ESP, that focuses on the specific needs of the skills and competences of the tourism professionals at various levels so that they would be able to develop language proficiency and acquire necessary competences for effective communication in English as required by the tourism industry. The survey employed questionnaires, informal discussions and interviews with the target group: lecturers, course coordinators, human resource managers and stakeholders, apart from analysis of text materials, i.e., syllabus, past question papers and answer scripts for data collection. Two hundred and twenty four (224) questionnaires were administered to these professionals as well as foreign tourists, and out of these 161 were completed and returned. The major findings of the study reveal that the academics in English are not aware of the specific needs of the undergraduates of tourism, 100% of the. undergraduates are weak in all four skills, and also the use of related vocabulary in tourism context, and the great majority of the tourism professionals are weak in communication skills. The findings also reveal that English plays a crucial role in the professional life of the tourism professionals since it is used extensively in conducting their day to day activities at the workplace.
Keywords: Communication, Competence, Tourism, Specific needs, Hospitality